The effects of detraining period on female basketball team players aged 10-12 - Emrah Atay; Gülsev Kayalarlı (Türk Spor ve Egzersiz Dergisi)
The purpose of the study is to find out the effect of break during the semester vacation on performance. 11women basketball players aged 11.45±0.82 years old, height 147.27±7.29 cm, weight 39.65±6.20 kg, sports age2.00±0.44 years participated in the study. Gülcü Primary School young women's basketball team, who trained 3times per week for about 6 months and came in first in the competition among Isparta primary schools, havetaken part in the study. The team was given pretest after the group's final match and afterwards the team took abreak from training. Second measurements were taken 20 days later. In order to determine changes in theperformance of the players, their resting heart rate, vertical jump, handgrip strength, flexibility, aerobicendurance and anaerobic endurance were examined. Descriptive statistics and Wilcoxon matched-pair twosample test were used for the analysis. It was observed that there was an increase in resting heart rates (p lt;0.05),decrease in vertical jump rates, aerobic endurance, anaerobic endurance (p lt;0.05). Hand grip strength did notchange significantly. According to the findings it can be concluded that, a break period for 20 days from trainingaffects the performance negatively For this reason, high-level performance aimed at primary school teams willneed to continue training during the semester break.